Pemaknaan Ruang Dalam pada Arsitektur Vernakular Jawa di Indonesia - Haryotedjo, Tri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The rapid flow of globalization has drowned out local cultural characteristics, thus blurring the identity of local architecture. Some architects seek to help preserve cultural heritage by incorporating Javanese vernacular architectural components into modern design structures. As a result, there is a visual blend of modern and traditional structures. This article aims to investigate the various uses of Javanese vernacular architecture in modern architectural projects, especially in buildings in the center of Kudus City. The systematic literature review (SLR) method is used to find practical theories related to the application of aesthetic aspects for modern architectural purposes. Another discovery concerns the understanding of the philosophical values inherent in existing vernacular building forms. Field observations are used to describe the observed situation in order to obtain primary data. The sample in the study included 4 traditional house locations in the city of Kudus.